2010
DOI: 10.1080/17543261003689888
|View full text |Cite
|
Sign up to set email alerts
|

3D CAD systems for the clothing industry

Abstract: The approaches to designing virtual garments may be categorised as "2D to 3D" and "3D to 2D". The former refers to draping flat digital pattern pieces on a virtual mannequin, and the later indicates the development of clothing design on a realistic body and subsequent flattening into 2D pattern pieces. Several CAD systems for garment visualisation in space from flat patterns have already been introduced into the clothing industry. Any industrial application of the pattern flattening technique is yet to be made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 30 publications
0
47
0
2
Order By: Relevance
“…According to Huang, Mok, Kwok, and Au (2012), CAD shortens the product development process allowing companies to bring products to market in a shorter time frame. It also offers greater cost efficiency and better communication among designers, manufacturers, and retailers (Sayem et al, 2010). Shan, Huang, and Qian (2012) state that CAD is widely used in the apparel industry for pattern drafting, grading, marker making, and textile design and illustration, and is crucial to the implementation of mass customisation.…”
Section: Computer-aided-designmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Huang, Mok, Kwok, and Au (2012), CAD shortens the product development process allowing companies to bring products to market in a shorter time frame. It also offers greater cost efficiency and better communication among designers, manufacturers, and retailers (Sayem et al, 2010). Shan, Huang, and Qian (2012) state that CAD is widely used in the apparel industry for pattern drafting, grading, marker making, and textile design and illustration, and is crucial to the implementation of mass customisation.…”
Section: Computer-aided-designmentioning
confidence: 99%
“…This process is much faster and more cost effective than traditional fitting on a live model (Cho, Park, Boeing, & Hingston, 2010). Virtual prototyping and virtual try-on can significantly reduce both time and costs of product development (Sayem et al, 2010). 3D garment design makes it possible to adjust garments designed for and sized to the firm's target customer to fit a potential customer who does not conform to the normal target size and shape (Li & Lu, 2011).…”
Section: D Garment Design and Pattern Draftingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the fitting process, 3D CAD systems are being introduced to the apparel industry. Several researchers (Sayem, Kennon, & Clarke, 2010) found that 3D CAD systems aided in visualization of the entire process from 2D pattern creation to the end product. However, according to Easters (2011), 3D human interaction technology is observed to be evolving slowly with limited success in the apparel industry.…”
Section: Significance Of Researchmentioning
confidence: 99%
“…Designers talk the language of aesthetics, creativity and fashion trends, whilst the manufacturing culture in the East is concerned with processes, resource allocation, material management and unit costs (Tyler, 2008, pp. For instance, between two and ten prototype iterations will be necessary in the current design development process (Sayem, Kennon, & Clarke, 2010). Lack of technical skill from designers in the West leads to ineffective design specifications, which are then lost in translation.…”
Section: Figure 2222mentioning
confidence: 99%